Implementasi Kumur Menggunakan Larutan Madu pada Penyembuhan Luka Abses Submandibula - Hariyani, Salsa Dila Fitria; Kosim, H (Journal of Telenursing (JOTING), 2025)
This study aimed to determine the effectiveness of honey gargling as a wound care method in patients with submandibular abscesses. The research methods included interviews, observation, physical examination, intervention recording, and daily evaluations. The gargling instruments included a honey solution and a Numeric Rating Scale (NRS). The results showed that patients who received non-pharmacological therapy by gargling with honey solution three times daily (morning, afternoon, and evening) by dissolving two spoons of honey in 200 ml of lukewarm water and holding it in their mouths for 30 seconds demonstrated a decrease in pain from 6 to 2, reduced swelling, disappearance of pus, and increased patient comfort. In conclusion, the healing process demonstrated good wound improvement. Honey gargling has been shown to support optimal wound healing, from the inflammatory phase, proliferation, to tissue maturation.   Keywords: Submandibular Abscess, Honey Gargle, Wound